Experimental evaluation on the power characteristic of direct-photovoltaic charging for thermal storage equipment - Reza Abdu Rahman; Sulistyo Sulistyo; Mohamad Said Kartono Tony Suryo Utomo; Dimas Ragil; Budhi Muliawan Suyitno (Universitas Muhammadiyah Magelang, 2024)
Thermal storage is an essential equipment for storing excessive heat, especially for water heating systems. The present work proposes a preliminary study to maximize the operation of thermal storage using photovoltaics as the primary source for charging the heat storage material. The assessment indicates the concept is feasible, where the output power from photovoltaics can be directly converted to heat using a heating element. The power ratio is considerably high (up to 38.6%), resulting in the maximum temperature of the heat absorber material (water) increasing to 43.2 °C. The final assessment using suitable phase transition material shows that steady phase behavior is essential to maximizing the temperature profile of the material. It is achieved using stabilized-hexadecanoic acid, which shows a transient phase transition at a temperature of 54.2 °C, reducing the possibility of heat loss with an average temperature rate of 0.54 °C/min in the discharge stage. This finding proves the proposed concept is applicable, while further improvement can be done to adjust the suitable power output from photovoltaic and storage tank arrangement for the actual system. Despite that, the result is expected to accelerate the utilization of photovoltaics as reliable solar renewable technology.